Bacteriological study in healthy carriers pregnant women and newborns at the Hospital San Bartolomé - Larrañaga Leguía, Alfredo (2015)
This form work and is the first part of an investigation initiated in our department in order to establish the morbidity, potential and actual, existing in these areas of work problem.